Case Report: Focal cryoablation vs. radiofrequency ablation in a pediatric patient with para-Hisian accessory pathway with effect from the non-coronary aortic cusp - Zhandos Maksut; Raushan Zhanbolatkyzy; Abay Bakytzhanuly; Almira Bajgalkanova; Yakup Ergül; Omirbek Nuralinov (Frontiers Media S.A., 2024)
A 12-lead electrocardiogram of a pediatric patient with Wolff-Parkinson-White syndrome was consistent with the anteroseptal accessory pathway. The patient had three ablation procedures because of the recurrences of the arrhythmia. In our case, successful cryoablation was performed in the non-coronary cusp of the aortic root.